1994
DOI: 10.1128/jb.176.14.4416-4423.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and mutational analysis of the hyb operon encoding Escherichia coli hydrogenase 2

Abstract: The genes encoding the two structural subunits of Escherichia coli hydrogenase 2 (HYD2) have been cloned and sequenced. They occur in an operon (hyb) which contains seven open reading frames. An hyb deletion mutant (strain AP3) failed to grow on dihydrogen-fumarate medium and also produced very low levels of HIYD1. All seven open reading frames are required for restoration of wild-type levels of active HYD2 in AP3.The hyb operon was mapped at 65 min on the E. coli chromosome.Under anaerobic growth conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 43 publications
4
141
0
Order By: Relevance
“…This led to the proposal that the function of hydrogenase 2 was in a respiratory capacity, allowing the cells to gain energy from the oxidation of molecular hydrogen. A subsequent mutational analysis of the hyb structural genes encoding the enzyme confirmed this hypothesis (Menon et al, 1994).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…This led to the proposal that the function of hydrogenase 2 was in a respiratory capacity, allowing the cells to gain energy from the oxidation of molecular hydrogen. A subsequent mutational analysis of the hyb structural genes encoding the enzyme confirmed this hypothesis (Menon et al, 1994).…”
Section: Introductionmentioning
confidence: 77%
“…Primer extension analysis using total RNA extracted from anaerobically grown cultures revealed a single 5h end ( The DNA sequence in the neighbourhood of the hyb operon transcription start site. The start site of transcription is located 102 bp upstream of the ATG translation initiation codon of the hybO gene (Menon et al, 1994 ;Sargent et al, 1998) and is indicated by the bent arrow. The putative k10 sequence upstream of the start site is underlined.…”
Section: Identification Of the Hyb Operon Transcriptional Start Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Fax: (33) 91 71 89 14. E-mail: wu@ibsm.cnrs-mrs.fr HYD2 and HYD3 activities, respectively [2][3][4][5]. All three hydrogenases contain nickel [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%